On propagation in networks, promising models beyond network diffusion to describe degenerative brain diseases and traumatic brain injuries - Vergni, Davide; Stolfi, Paola; Pascarella, Annalisa (Frontiers in Pharmacology, 2024)
Connections among neurons form one of the most amazing and effective network in nature. At higher level, also the functional structures of the brain is organized as a network. It is therefore natural to use modern techniques of network analysis to describe the structures of networks in the brain. Many studies have been conducted in this area, showing that the structure of the neuronal network is complex, with a small-world topology, modularity and the presence of hubs. Other studies have been conducted to investigate the dynamical processes occurring in brain networks, analyzing local and large-scale network dynamics. Recently, network diffusion dynamics have been proposed as a model for the progression of brain degenerative diseases and for traumatic brain injuries. In this paper, network diffusion dynamics will be re-examined and other network dynamics will be proposed to accurately describe degenerative dynamics in the brain network.